Direction of arrival estimation using the rotating equatorial microphone - Lawrence, Jeremy; Ahrens, Jens; Peters, Nils (Frontiers in Signal Processing, 2024)
Direction of arrival (DOA) estimation of sound sources is an essential task of sound field analysis and typically requires two or more microphones. In this study, we present an algorithm that allows for DOA estimation using the previously designed Rotating Equatorial Microphone prototype, which is a single microphone that moves rapidly in a circular fashion, introducing DOA-dependent periodic distortions in the captured signal. The proposed algorithm compensates for the induced spectral distortions to estimate the DOA. The approach is verified by numerical simulations and practical experiments in a low-reverberant environment. Whilst previous work only allowed for the localization of a single monochromatic sound source with a known frequency, our approach can localize single unknown wideband sources with a mean absolute error of 5.4 degrees in practice.Two sources are also localizable provided they are sufficiently separated in space.